2011
DOI: 10.1091/mbc.e11-04-0287
|View full text |Cite
|
Sign up to set email alerts
|

Nesprin-3 regulates endothelial cell morphology, perinuclear cytoskeletal architecture, and flow-induced polarization

Abstract: Nesprin-3, a protein that links intermediate filaments to the nucleus, plays a role in vascular endothelial cell (EC) function. Nesprin-3 regulates EC morphology, perinuclear cytoskeletal organization, centrosome–nuclear connectivity, and flow-induced cell polarization and migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 63 publications
1
99
0
Order By: Relevance
“…Vascular endothelial cells are known to alter their shape in response to diverse factors such as mechanical and biochemical stimuli, which influence a variety of cellular functions (47). In this study, we observed that knockdown of TRPM7 dramatically alters the morphology of HUVECs: they change from flat and rounded shape to constricted and elongated morphology.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Vascular endothelial cells are known to alter their shape in response to diverse factors such as mechanical and biochemical stimuli, which influence a variety of cellular functions (47). In this study, we observed that knockdown of TRPM7 dramatically alters the morphology of HUVECs: they change from flat and rounded shape to constricted and elongated morphology.…”
Section: Discussionmentioning
confidence: 64%
“…As a change in cell shape directly affects cell function including proliferation, apoptosis, and inflammation in various cell types (8,9,47,70), the change in the morphology of HUVECs induced by knockdown of TRPM7 suggests that TRPM7 may play an important role in regulating the functions of endothelium under physiological and pathological conditions. Our data suggest that a reduced level of TRPM7 might facilitate the vascular repair in case of damage through enhanced angiogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental differences in anchoring to the microtubule cytoskeleton can also be seen in this organism: in embryos, the KASH protein ZYG-12 is required for localization of dynein and centrosome tethering via SUN-1, but in epidermal hypodermal precursor cells the KASH protein UNC-83 and the SUN protein UNC-84 are important for microtubule tethering in a centrosome-independent pathway [56,71]. In cultured mammalian neurons, glial cells or kerotinocytes, Sun1/2 and the KASH proteins Syne/Nesprin-1/2 make the connection between the centrosome and the nucleus, while centrosome tethering in human aortic endothelial cells is dependent on nesprin-3 and intermediate filaments [58,69,[72][73][74]. However, studies in HeLa cells reveal a dependence on nucleoporins for centrosome tethering at the NE while reports from human and murine fibroblast investigations have shown the INM protein emerin mediates the centrosome-NE attachment through an interaction with tubulin [69 ,75,76].…”
Section: Centrosomes and Nuclear Envelope Breakdownmentioning
confidence: 99%
“…Through the plectin-binding domain, Nesprin-3 can connect the NE to the intermediate fi lament system [ 7 ]. Nesprin-3 defi ciency leads to reduced amounts of perinuclear intermediate fi laments as shown in zebrafi sh [ 8 ] or human aortic endothelial cells [ 9 ]. Finally, Nesprin-2 and -4 interact with the microtubule network through interactions with the microtubule motor protein Kinesin-1 [ 10 , 11 ].…”
Section: Nesprinsmentioning
confidence: 99%